Analisis Spasial Potensi Daerah Resapan Air Di Daerah Airan Sungai Tangka Provinsi Sulawesi Selatan - Nasiah Badwi; Ichsan Invanni; Irwansyah Irwansyah (UNIVERSITAS NEGERI MAKASSAR, 2023)
Water is a very vital need in life, there is no water, living things will become extinct. As the population grows, the need for water increases, where the availability of water is limited. To meet water needs in the dry season, groundwater sources are needed. Groundwater potential is determined by the level of water that experiences infiltration. This study aims to describe the potential of the infiltration area. The method used is Geographic Information System. There are 5 overlaid variables, namely; rainfall, slope, rock type, soil type, and land use. The results of the study describe that there are 3 classes of potential catchment areas in the Tangka watershed, namely: high, medium and low. Most of the area is in the medium class area of 38,434.73 Ha or 80.69 percent spread from upstream to downstream covering all districts, namely: Tinggimoncong, Tombolopao, West Sinjai, Bulupoddo, Bontocani, Kajuara and North Sinjai. The very high class area is only 2,110.62 hectares or 4.43 percent spread over the Tinggimoncong, Tombolopao, Kahu, Kajuara and North Sinjai sub-districts. Low absorption potential in the middle of the watershed covers the northern part of Kunciopao, West Sinjai, Bontocani, and Bulupoddo Districts.